Coronavirus disease (COVID-19): observations and lessons from primary medical care at a German community hospital. Issue 2 (3rd March 2020) - Schiller, Martin; Fisahn, Juergen; Huebner, Ute; Hofmann, Patrick; Walther, Joerg; Riess, Susann; Grimm, Christiane; Schwab, Hansjörg; Kick, Wolfgang
ABSTRACT: The pandemic outbreak of COVID-19 challenges medical care systems all around the world. We here describe our experiences during the treatment of COVID-19 patients (n = 42) treated from 2 March 2020 to 16 April 2020 at a German district hospital. Forty-two COVID-19 patients were hospitalized and five patients developed a severe disease, requiring intensive care. Overall, 11 out of 42 hospitalized patients died. COVID-19 caused lymphocytopenia, as well as increased d-dimer, c-reactive protein and creatine kinase, and lactate dehydrogenase levels. These changes were mostly pronounced in patients that developed a severe disease course. Radiologic findings included ground-glass opacity, bilateral/multilobular involvement, consolidation, and posterior involvement. We compared COVID-19 patients to an average population of 'non-COVID' patients. Interestingly, no laboratory or radiologic finding was specific for COVID-19 when standing alone, as comorbidities of 'non-COVID' patients certainly can mimic similar results. In common praxis, the diagnosis of COVID-19 is based on a positive PCR result. However, a false-negative result causes problems for the workflow of an entire hospital. In our clinic, the consequences of a false assumption of SARS-CoV-2 negativity in four cases had dramatic consequences, as contact persons had to be quarantined. To avoid this, a comprehensive view of lab-results, radiology, clinical symptoms and comorbidities is necessary for the correct diagnosis or exclusion of COVID-19.